Walory poznawcze reportaży radiowych w świetle dotychczasowych badań naukowych - Czarnek, Paulina (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2011)
Despite the fact that radio documentaries broadcast mainly strong emotions, news values of this genre are also its essential feature. Therefore, it is necessary to describe the potential of such works to deliver knowledge about the transcendent world, which could be significant for the listeners. The aim of this article is to show theses made by scholars as regards radio documentaries. Researchers’ analyses are related to the genre’s potential possibilities of to broaden people’s minds and influence the recipient’s perception.